A long-term recurrence-free survival of a patient with the mixed adeno-neuroendocrine bile duct carcinoma: A case report and review of the literature. (2017) - Izumo, Wataru; Higuchi, Ryota; Yazawa, Takehisa; Uemura, Shuichiro; Matsunaga, Yutaro; Shiihara, Masahiro; Furukawa, Toru; Yamamoto, Masakazu
Highlights: Mixed adeno-neuroendocrine carcinoma arising primarily in the bile duct is very rare neoplasm. The patient with mixed adeno-neuroendocrine carcinoma in the bile duct indicates a poor prognosis. On imaging studies, a hypervascular tumor is suspicious of mixed adeno-neuroendocrine carcinoma. Curative resection is the only way to obtain the long-term prognosis, even if these patients have lymph node metastasis. Abstract: Introduction: Neuroendocrine tumors arising primarily in the bile duct are rare. And among these tumors, mixed adeno-neuroendocrine carcinoma (MANEC) is quite uncommon. We report a patient with MANEC who achieved long-term recurrence-free survival. And our case report includes analysis previous case reports. Presentation of case: A 66-year-old man underwent investigation for persistent anorexia and fatigue. Laboratory tests showed that the values of hepatobiliary enzymes were increased. On CT, a 10 mm × 8 mm hypervascular tumor was observed in the distal bile duct and the proximal bile duct was markedly dilated. Endoscopic retrograde cholangiography (ERC) also showed a stenosis with a long diameter of 10 mm. Examination of a biopsy specimen obtained from the narrow site of the bile duct at the time of ERC revealed tubular adenocarcinoma. Therefore, pylorus-preserving pancreaticoduodenectomy was performed under a preoperative diagnosis of distal bile duct carcinoma. Postoperative pathologic examination revealed alveolar structures and a mixture of moderately differentiated adenocarcinoma with synaptophysin-positive and chromogranin-A-positive neuroendocrine carcinoma. Therefore, the final diagnosis was MANEC, pT3, pN1, M0, pStage II B (TNM classification of the UICC). Curative resection was achieved and there has been no recurrence after 30 months. Discussion: In the previous reports, only five patients (14.7%) survived for 24 months or longer. Median survival was longer (14 months) in the curative resection group and shorter (6 months) in the non-curative resection group. Conclusion: Curative resection is essential to achieve long-term survival in patients with bile duct MANEC, even if these patients have lymph node metastasis.